Evaluation of the efficacy of XP-endo Finisher, Easy Clean, Passive ultrasonic irrigation, and conventional irrigation in the removal of calcium hydroxide in simulated internal root resorption cavities (Research, Society and Development, 2021)
This study aimed to evaluate the efficacy of 5 irrigation protocols in removing calcium hydroxide in simulated internal root resorption cavities. Eighteen extracted human teeth, upper anterior and uniradicular, were prepared up to size 50. The teeth were divided longitudinally, and internal root resorption cavities were made by acid demineralization using nitric acid. The same sample was submitted to the five irrigation protocols. The cavities and root canals were filled with Ultracal XS (Ultradent, South Jordan, UT, USA) and stored in an incubator at 37ºC for one week. Afterward, the irrigation protocols were carried out: XP-endo Finisher (XPF; FKG, La Chaux-de-Fonds, Switzerland), passive ultrasonic irrigation (PUI), Easy Clean (Bassi/Easy Equipamentos Odontológicos, Belo Horizonte, Brazil) with reciprocating movement (ECR), Easy Clean with continuous rotation (ECC) and conventional irrigation with a syringe (CI). The solutions used, 2.5% NaOCl, and 17% EDTA, were warmed. The total volume of irrigant used for each sample was 20 mL (10 mL of 2.5% NaOCl, 5 mL of 17% EDTA and 5 mL of distilled water). The amount of calcium hydroxide remaining in the internal resorption after irrigation was assessed using scores. The data were analyzed using the Pearson and Kruskal-Wallis (Dunn) tests. Significantly more calcium hydroxide was removed in the XPF group than all other sample groups (P < 0.0001). XPF was superior to the other methods tested to remove calcium hydroxide in teeth with simulated internal resorptions.